2018
DOI: 10.3926/jiem.2558
|View full text |Cite
|
Sign up to set email alerts
|

The impact of relational governance on performance improvement in export manufacturing firms

Abstract: Purpose: This paper seeks to identify the factors affecting social performance improvemens in the Pakistan export manufacturing firms and investigae inter-relationships existing among them.Design/methodology/approach: This study used a cross-sectional survey; data were collected using self-administered survey questionnaire. Using data collected from 239 small- and medium-sized direct exporters manufacturing firms in Pakistan. We used structural equation modelling (SEM) approach to test structural model, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 85 publications
0
60
0
Order By: Relevance
“…Cultural intelligence research has shown that each dimension of CQ is sharply different and each of these dimensions affects intercultural interaction [51]. Some studies endorse that CQ is an important strategy in safeguarding cooperation to apply one's own cultural knowledge in cross-culture interaction for minimizing differences [4]. Previous research has not shown clearly which dimensions of CQ are critical for collaboration [28].…”
Section: Meta-cognitive and Cognitive Cqmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultural intelligence research has shown that each dimension of CQ is sharply different and each of these dimensions affects intercultural interaction [51]. Some studies endorse that CQ is an important strategy in safeguarding cooperation to apply one's own cultural knowledge in cross-culture interaction for minimizing differences [4]. Previous research has not shown clearly which dimensions of CQ are critical for collaboration [28].…”
Section: Meta-cognitive and Cognitive Cqmentioning
confidence: 99%
“…Chua et al (2012) [28] found that high metacognitive CQ had a direct effect on collaboration in cross-cultural interactions. Cognition and meta-cognition enable managers to monitor one's knowledge process deliberately and to regulate these states to achieve greater adaptation to some objectives [4,56]. As an illustration, Crotty and Brett (2012) [57] highlighted the significance of self-awareness and consciousness of other reactions in handling foreign collaborative culture.…”
Section: Meta-cognitive and Cognitive Cqmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has provided evidence that supplier development initiatives have been fruitful in upgrading supplier performance [4,5]. Despite considerable research on environmental sustainability in the supply chain relationship, the supplier-side of knowledge acquisition for social sustainability has mostly been ignored [6]. The study on how the buyer enables knowledge enrichment activities affects the firm peripheries, and the development of new activities is still in inception [7].…”
Section: Introductionmentioning
confidence: 99%
“…The specialties of professionals may also expand because of their sharing different views, which results in increased job satisfaction. For example, it has been found that the involvement of suppliers of products and services in a collaborative model can result in higher social sustainability performance as they share knowledge, and work jointly to create value and improve social performance [83][84][85]. Therefore, the next proposition can be advanced: Proposition 6.…”
Section: Collaborative Healthcare and Social Sustainabilitymentioning
confidence: 99%